ANALISIS PENGARUH SUKU BUNGA, INFLASI DAN PENDAPATAN PERKAPITA TERHADAP KREDIT TERSALUR PADA BANK PEMERINTAH DI KALIMANTAN BARAT - B01107078, Pontya Novresia Osyi (Jurnal Pembangunan dan Pemerataan, 2012)
This study entitled "The Effect of Interest Rates, Inflation and the per capita income to Credit channeled the State Bank in West Kalimantan". The problem in this study was "Is there any effect of interest rates, inflation and per capita income on loans at state banks in West Kalimantan". While the goal of this research is to examine and analyze the effect of interest rates, inflation and per capita income of the loan lending. The model used in this study is the multiple linear regression models using econometric approaches and methods used are associative method to see the effect or the relationship between interest rates, inflation and per capita income to West Kalimantan. From the research that has been done can be concluded that the interest rate (X1) significantly affects the amount of bank lending to the government in West Kalimantan, while inflation and per capita income are not significant.